STEM and gender issues: A systematic review (Revista Contexto & Educação, 2025)
In the present study, a systematic review of the literature was prepared, based on data from the SciELO, Web of Science, and IEEE Xplore platforms. This procedure allowed for an analysis of the picture relating the STEM approach to multiculturalism, particularly with issues of gender inequality in STEM careers. The aforementioned platforms were initially consulted to create the corpus. Among the selected articles (43), more than half (22) addressed gender issues. In the articles described, a behavioral trend was clear that would lead women to become discouraged concerning their identification with STEM careers. It was observed that gender inequality in STEM areas is not an isolated fact, but is present in several countries and different realities. In all of them, this inequality converges from preconceived positions and statements that supposedly indicate women's lack of interest in STEM careers or, what is worse, a belief of the supposed innate inability to do so. The studies indicated that there is an evident need for public policies aimed at gender equity and the participation of women in STEM careers.
Keywords: STEM; gender; multiculturalism